A rare case of orbital melanoma: chronicle of the eye - Murkhe, Alind V.; Shukla, Ajay Kumar; Sheikh, Azhar; Shahare, Monika (International Journal Of Community Medicine And Public Health, 2025)
Melanoma is a malignancy of melanocytes and can present as a primary malignancy, secondary malignancy due to local extension, or metastatic lesion from a distant primary lesion. A 75 years old male visited the eye OPD and reported experiencing painful loss of vision in his right eye and proptosis for the past 2 months. Visual acuity of right eye was no perception of light. There was abaxial proptosis (inferomedial) of right eye with gross lid edema along with conjunctival chemosis. MRI scan orbit reveals large heterogeneously enhancing soft tissue density lobulated mass of approximate size 4.4×3.4× 2.9 cm noted in right orbit, involving posterior wall of right eyeball, displacing it medially and causing proptosis, with hyperintensese areas within the vitreous chamber of right eyeball. Patient underwent right orbital subtotal exenteration and the specimen sent for histopathological examination revealed malignant melanoma of right orbit involving choroid and infiltrates all structure of globe. Patients who present with imaging evidence of a well-defined tumour and unilateral proptosis should be evaluated for the rare cancer known as primary orbital melanoma. An aggressive and multidisciplinary approach is needed in management of this tumour.